Binnen en Buiten : Vluchtelingen op zoek naar rechten - Bossuyt, Jean; Coenegrachts, Kris; De Feyter, Koen; Denys, Luc; De Wit, John; Hobin, Veerle; Moussalli, Michel; Van Cauwenberge, Katie; Vanden Bon, Alain; Walleyn, Luc (Antwerpen: Kluwer, 1988)
"Jean Bossuyt, Kris Coenegrachts, Koen De Feyter, Luc Denys, John De Wit, Veerle Hobin, Michel Moussalli, Katie Van Cauwenberge, Alain Vanden Bon, Luc Walleyn Dossier Liga voor Mensenrechten"